Measuring the Impact of Growth and Income Distribution on Poverty in India - Dhongde, Shatakshee (Journal of Income Distribution®, 2007)
Since the economic reforms of the early 1990s, the Indian economy witnessed a rapid rise in the mean income level, and, simultaneously, changes in the distribution of income. This study tries to capture how these changes affected poverty levels across major states in India. Total change in poverty is decomposed into the changes due to a rise in the mean income level and due to changes in the distribution of income. It is observed that, in India, rapid growth led to a significant decline in poverty though changes in the distribution of income which adversely affected the poor.